GAMS – An infrastructure for the long-term preservation and publication of research data from the Humanities - Johannes Hubert Stigler; Elisabeth Steiner (Mitteilungen der Vereinigung Österreichischer Bibliothekarinnen und Bibliothekare, 2018)
Research data repositories and data centres are becoming more and more important as infrastructures in academic research. The article introduces the Humanities’ research data repository GAMS, starting with the system architecture to preservation policy and content policy. Challenges of data centres and repositories and the general and domain-specific approaches and solutions are outlined. Special emphasis lies on the sustainability and long-term perspective of such infrastructures, not only on the technical but above all on the organisational and financial level.